Digital India Programme: Going Full Circle - Abhishek Beriya (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2021)
The Digital India programme of the government of India, launched in 2015, is an ambitious initiative which seeks to effect both process improvements as well as transform governance for the future in India through massive digitisation efforts. Numerous initiatives, particularly in the works of the Indian federal government have been initiated and have also delivered successful outputs and outcomes. Digitisation efforts are also being applied to comprehensively cover the functioning of local self-governance institutions like the Panchayats for easing processes as well as enhancing transparency aspects in their day-day operations. In the sense of coverage, thus, the Digital India Programme has come full circle. Apart from the usual challenges in any government programme of scale in India, like economic costs, illiteracy etc., lack of digital literacy, attitude of citizens as well as government departments and personnel resisting change, redressal of digital grievances, wide range of cyber-crimes and policy issues emerge as the major challenges facing Digital India. Continued support to Digital India, from both the federal as well as state governments is therefore necessary to achieve its objectives comprehensively.
Keywords: 330